2006
DOI: 10.1096/fj.05-4493com
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐angiogenesis therapy can overcome endothelial cell anergy and promote leukocyte‐endothelium interactions and infiltration in tumors

Abstract: Tumor escape from immunity, as well as the failure of several anti-cancer vaccination and cellular immunotherapy approaches, is suggested to be due to the angiogenesis-mediated suppression of endothelial cell (EC) adhesion molecules involved in leukocyte-vessel wall interactions. We hypothesized that inhibition of angiogenesis would overcome this escape from immunity. We investigated this in vivo by means of intravital microscopy and ex vivo by immunohistochemistry in two mouse tumor models. Angiogenesis inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
191
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(197 citation statements)
references
References 33 publications
4
191
0
2
Order By: Relevance
“…20--22 Leukocyte--vessel wall interactions are mediated by endothelial cell adhesion molecules, such as intercellular adhesion molecule-1 and -2 (ICAM-1 and ICAM-2), vascular cell adhesion molecule-1 (VCAM-1), E-selectin and CD34. 23 Dikxs et al 24 have demonstrated that angiogenesis inhibitors increase leukocyte--vessel wall interactions in tumor vessels, which lead to increased leukocyte infiltration into tumor tissue. Endogenous inhibitors of angiogenesis are proteins or protein fragments that are formed in the body and can inhibit the formation of blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…20--22 Leukocyte--vessel wall interactions are mediated by endothelial cell adhesion molecules, such as intercellular adhesion molecule-1 and -2 (ICAM-1 and ICAM-2), vascular cell adhesion molecule-1 (VCAM-1), E-selectin and CD34. 23 Dikxs et al 24 have demonstrated that angiogenesis inhibitors increase leukocyte--vessel wall interactions in tumor vessels, which lead to increased leukocyte infiltration into tumor tissue. Endogenous inhibitors of angiogenesis are proteins or protein fragments that are formed in the body and can inhibit the formation of blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Immortalized human fetal tracheal cells (CFT-2, cell line carrying the homozygous mutation DF508, and NT-1, control cell line) were previously characterized [7,8]. Human umbilical vein endothelial cells (HUVEC) were isolated and cultured as previously described [9]. Only cells from passage 1 to 3 were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A few experimental studies have shown that endogenous T cell infiltration is increased following anti-angiogenic agents [153][154][155], and one study has shown that the efficacy of DC101 treatment is dependent on both CD4 + and CD8 + T cells in a transplantable mammary tumor model [153]. As such, the need for more investigations into the role of immunosuppressive and adaptive immune cells is warranted to help guide the future clinical possibility of combining vascular-targeting agents with immunotherapy.…”
Section: Much Less Is Known About the Role Of Tregs And T Cells Durinmentioning
confidence: 99%